The Crystal Circe - Kuttner, Henry, 1915-1958; Musacchia, John B., 1916-2004 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Crystal Circe" by Henry Kuttner is a science fiction novel published in the early 1940s. The story centers on themes of alien life and obsession as it follows the protagonists, Steve Arnsen and Douglas O'Brien, who discover a mysterious crystal from a meteorite. This gem leads them to experiences beyond their understanding and reveals a profound connection to a goddess-like figure named Circe. The narrative unfolds as Arnsen and O'Brien embark on an adventurous journey through space, driven by O'Brien's obsession with the crystal and his belief in the existence of Deirdre, a beautiful otherworldly being. As they travel through the unknown, O'Brien disappears after being enchanted by Circe, leading Arnsen to confront the reality of their situation and the true nature of Circe and the crystals. The story culminates in themes of sacrifice and loss, as Arnsen grapples with his own feelings of longing and the consequences of their voyage, ultimately deciding the fate of himself and the alluring yet dangerous Circe. The haunting exploration of love, sacrifice, and the mystical intertwines throughout this tale, prompting profound reflection on the nature of existence and the seductive pull of the unknown. (This is an automatically generated summary.)
Release date is 2022-08-11
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Male friendship -- Fiction; Storytelling -- Fiction; Human-alien encounters -- Fiction; Asteroids -- Fiction; Meteorites -- Fiction